The Effect Of General Allocation Funds And Special Allocation Funds On Regional Expenditures Is Unclear (Study on Cities and Regencies in Bengkulu Province) - Putra, Trio Ade; Soleh , Ahmad; Made ER.M.G , Ida Ayu (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the effect of the General Allocation Fund (DAU) and the Special Allocation Fund (DAK) on regional expenditures for cities in Bengkulu and the province. The population of this survey is all districts/cities in Bengkulu from 2015 to 2020 and includes a sample of 10 districts/cities. Data collection technology uses documentation technology with quantitative collection methods. All data processing in this study was assisted by the use of data processing software SPSS (Statistical Product and Service Solutions) version 22. The results showed that the General Allocation Fund (DAU) (X1) had a significant effect on regional spending (Y), with a coefficient value of 14,498, a significance value of 0.000 < 0> Ftable, then a value of 154,395 > 4,10. show.